MORFOLOGI ALUN-ALUN LASEM - Santoso, Rohman Eko; Sari, Suzanna Ratih; Rukayah, R. Siti (Jurnal Arsitektur ARCADE, 2020)
Lasem is a sub-district on the east side of Rembang regency which is directly adjacent to the province of East Java. Lasem Square has existed since the kingdom era in 1513 and is constantly undergoing changes followed by a reduction in the area, function and activities therein. Along with the shrinking area and even the disappearance of the square that occurred from time to time, it is necessary to research the typology and morphology of the square to be used as a basis for revitalizing the Lasem square. This study aims to analyze the morphology of the Alun-alun Lasem, using historical reference data, books, field surveys, interviews, mapping and digitizing. In this study using descriptive qualitative analysis methods, as ingredients to add analysis based on field findings. Based on the results of this study it was found that the Typology and Morphology of the Lasem Square was influenced by government and ruling policy factors in its era. This is indicated by the changes in the square in terms of the extent, functions and activities that exist within and in the supporting area and its surroundings.